Effectiveness of Community-Based Psychosocial Crisis Intervention in Elderly and Future Research Directions: Scoping Review - Raharjo, Alim Panggih; Amalia, Adina Hafidhah; Aulia, Salsabila Zahra; Prabaningtyas, Farisha Dian; Evitananda, Shella; Zhafirah, Andi Alya; Putri, Ivanka Natalia Elga Hamiseno (Faculty of Psychology Universitas Gadjah Mada, 2024)
Psychosocial crises in the elderly can cause trauma, life crises, and disrupt psychological well-being. The elderly are vulnerable to psychosocial crises, so interventions are needed to prevent or solve problems. This study aims to determine the types of community-based psychosocial crisis interventions for the elderly. Based on a literature search on five databases, nine studies were found in the last five years that used community-based psychosocial crisis interventions and proved to be effective in the elderly. The programs included C4C, Assistive Technology Application, Qigong, Gardening, CCP, SoBeezy, Dance, BAILAMOS™, and WE-RISE. Some of the intervention programs were used for the elderly with a diagnosis of mental illness and the general elderly. Community-based psychosocial crisis interventions are effective in older adults with or without a history of mental illness This study also offers future research directions for further research.